STRUCTURE OF THE MANAGEMENT SYSTEM FOR RESOURCES AND INFORMATION PROCESSES OF ENTERPRISES - ABUSHOV, Teymur (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The effectiveness of economic activity depends on various factors, one of which is the level of management of all resources. With the change in socio-economic relations, the importance of certain types of resources has changed, and a new type of resources has appeared - information resources. However, under any conditions, the effectiveness of enterprise resource management directly affects the efficiency and profitability of the business. Management activities regarding resource management require systematicity and involve analyzing the state of available resources, determining the need for various types of resources in accordance with the development strategy and plans of the enterprise, organizing the activities of the enterprise to provide resources to all divisions of the enterprise. In addition, the resource management system should provide a flexible mechanism for responding to changes in the operating environment and making appropriate corrective decisions. This can be achieved by forming an integrated system of resource management and information processes of enterprises, the main advantage of which is the information environment formed around business processes, which ensures the use of information as one of the strategic resources. Within this system, it is advisable to distinguish theoretical, methodological, organizational and infrastructure blocks, which together ensure the possibility of continuous activity of the business entity. The key to the success of the specified management system is the involvement of the team in the management process, continuous training of personnel, including the formation of incentives for self-development. In addition, one of the areas of training should be considered information resource management, including data protection, which is an important prerequisite for protection against cyber threats. The key task of the specified system is the most efficient use of all resources, which also implies the desire for minimal impact on the environment. In the context of resource conservation and compliance with the principle of climate neutrality, maximum energy-saving production is especially important.
Keywords: resource management; information processes; integrated management system; management methods; resource management functions